Community Empowerment Via Academic-Community Partnerships In Tourism Event Management: A Case Study Of Lanta Nice Beach Resort - Bagus, Alif; Rohim, Abdul; Khazinatul Khaeriah, RD. Hera merdeka; Hayati, Asfitri (Community Services and Social Work Bulletin, 2025)
Lanta Nice Beach Resort demonstrates significant potential for sustainable tourism growth through strategic collaboration between university students and the local community. This study examines a community-based event development initiative, wherein multidisciplinary students engage in capacity-building programs to enhance local tourism attractiveness. The program employed a combination of workshops, discussions, and practical training focused on event planning, marketing strategies, and operational execution. Data were collected through participant surveys and program evaluations to assess knowledge acquisition and perceived benefits. Findings reveal that over 80% of participants reported improved understanding of tourism event management, while 90% acknowledged tangible benefits for local tourism development. Key outcomes include the design of flagship events, such as cultural festivals and art performances, intended to attract both domestic and international visitors. Furthermore, active community participation reflects increased awareness of local cultural identity and the importance of sustainable tourism practices. This research highlights the efficacy of student-community collaboration in co-creating tourism experiences that stimulate economic development, foster cultural preservation, and enhance visitor engagement. The study provides actionable insights for policymakers and practitioners seeking to implement community-driven tourism initiatives in coastal destinations, emphasizing the integration of educational resources with local stakeholder engagement to achieve long-term tourism growth.